2011
DOI: 10.1007/s00280-011-1684-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating rational non-cross-resistant combination therapy in advanced clear cell renal cell carcinoma: combined mTOR and AKT inhibitor therapy

Abstract: Purpose Inhibition of the mammalian target of rapamycin (mTOR), a regulator of hypoxia inducible factor (HIF), is an established therapy for advanced renal cell cancer (RCC). Inhibition of mTOR results in compensatory AKT activation, a likely resistance mechanism. We evaluated whether addition of the Akt inhibitor perifosine to the mTOR inhibitor rapamycin would synergistically inhibit RCC. Methods Select RCC cell lines were studied [786-O, A498 (VHL mutant), CAKI-1 (VHL wild type), and 769-P (VHL methylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Furthermore, many investigators have demonstrated additive benefits from combining perifosine with a rapalogue in preclinical studies of multiple tumor types, including RCC. [20][21][22] These findings, combined with the observation that perifosine is very well tolerated with toxicities that generally do not overlap with those of VEGF antagonists and rapalogues, suggest that perifosine may be an attractive agent to assess clinically in combination with currently available agents in RCC. Indeed, a clinical trial is already underway combining perifosine with temsirolimus in patients with malignant glioma (National Clinical Trial identifier NCT01051557).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, many investigators have demonstrated additive benefits from combining perifosine with a rapalogue in preclinical studies of multiple tumor types, including RCC. [20][21][22] These findings, combined with the observation that perifosine is very well tolerated with toxicities that generally do not overlap with those of VEGF antagonists and rapalogues, suggest that perifosine may be an attractive agent to assess clinically in combination with currently available agents in RCC. Indeed, a clinical trial is already underway combining perifosine with temsirolimus in patients with malignant glioma (National Clinical Trial identifier NCT01051557).…”
Section: Discussionmentioning
confidence: 95%
“…1). ACHN and Caki-1 cells are wild type, whereas the 786-O cell line is mutated for VHL (Stickle et al, 2005;Ishimaru et al, 2010;Holland et al, 2012). Moreover, 786-O cells are deficient in PDGFR-b, which is the target molecule of sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the assumption that an Akt inhibitor may simply be a better mTOR inhibitor in RCC may not be valid. Indeed, many investigators have shown additive benefits from combining perifosine with a rapalogue in preclinical studies in multiple tumor types including RCC and similar clinical studies are underway [46][47][48]. Given the aforementioned observation that perifosine is very well tolerated with toxicities which are in general non-overlapping with those of VEGF-antagonists and rapalogues, it likely remains that the future of perifosine in RCC is not as a single-agent, but in combination with other molecularly targeted agents, particularly the rapalogues.…”
Section: Expert Opinionmentioning
confidence: 98%